2020
DOI: 10.1186/s12885-020-6628-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of gamma-glutamyl transpeptidase to lymphocyte count ratio in hepatocellular carcinoma patients with microvascular invasion

Abstract: Background: Microvascular invasion (MVI) is an independent risk factor for poor prognosis in hepatocellular carcinoma (HCC). However, there is still a lack of preoperative markers to predict MVI in HCC. This study intends to explore the potential application value of the gamma-glutamyl transpeptidase (GGT) to lymphocyte count ratio (GLR) in predicting MVI in HCC and provide guidance for clinical diagnosis and treatment. Methods: From March 2010 to December 2015, 230 HCC patients who underwent surgical treatmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…High GPR (> 0.23) was an independent risk factor for hepatocellular carcinoma development in chronic hepatitis patients [ 17 ]. High GLR was also an independent prognostic factor of hepatocellular carcinoma and intrahepatic cholangiocarcinoma [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High GPR (> 0.23) was an independent risk factor for hepatocellular carcinoma development in chronic hepatitis patients [ 17 ]. High GLR was also an independent prognostic factor of hepatocellular carcinoma and intrahepatic cholangiocarcinoma [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…GPR and GLR were calculated as GGT/ULN of GGT/platelet count (10 9 /L)×100 [ 2 ] and as the ratio of GGT to lymphocyte cell count [ 8 ], respectively. The samples were excluded with White blood cell (WBC) less than 3.5 × 10 9 /L or more than 9.5 × 10 9 /L, lymphocyte less than 1.1 × 10 9 /L or more than 3.2 × 10 9 /L and platelet less than 125 × 10 9 /L or more than 350 × 10 9 /L and hepatic insufficiency with GGT more than 100 U/L.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 In recent years, several studies have used a combination of different routine laboratory inflammatory markers to predict MVI before surgery. Previous studies have demonstrated that some preoperative inflammatory markers can be used to predict MVI in patients with HCC, such as the neutrophil-to-lymphocyte ratio (NLR), 8 platelet-to-lymphocyte ratio (PLR), 9 alkaline phosphatase (ALT)-to-lymphocyte ratio (ALR), 10 gamma-glutamyl transpeptidase (GGT)-to-lymphocyte ratio (GLR), 11 and lymphocyte-to-monocyte ratio (LMR). 12 Recently, some studies have reported that the GGT-to-platelet ratio (GPR), 13 aspartate aminotransferase (AST)-to-platelet ratio (APR), 14 and GGT-to-albumin ratio (GAR) 15 are independent risk factors that influence the prognosis of patients with HCC after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that AFP-L3 and protein induced by Vitamin K absence or Antagonist-II (PIVKA-II) have high specificity in the diagnosis of HCC (92.9% and 89%, respectively), but the sensitivity of these individual serum markers for early HCC diagnosis is suboptimal [ 11 , 12 ]. Furthermore, combined indicators such as neutrophil–lymphocyte ratio (NLR) [ 13 ], gamma-glutamyl transpeptidase to platelet ratio (GPR) [ 14 ], and gamma-glutamyl transpeptidase to lymphocyte ratio (GLR) [ 15 ] can be used to predict the prognosis and onset of HCC. Some studies have developed score models based on different variables such as gender, age, AFP levels, and pathological data, which have improved the accuracy of early HCC diagnosis.…”
Section: Introductionmentioning
confidence: 99%